A preliminary study of new single polymorphisms in the T helper type 17 pathway for psoriasis in the Korean population. (24th November 2016) - Kim, S Y; Hur, M S; Choi, B G; Kim, M J; Lee, Y W; Choe, Y B; Ahn, K J
Summary: Psoriasis is a polygenic and multi-factorial disease showing ethnic differences in terms of its severity and frequency. Therapies targeting interleukin (IL)−17A, IL-17 receptor (IL-17R) and Janus kinases (JAKs) are in clinical development for the treatment of psoriasis, and their success suggests the essential role of these molecules in psoriasis. To investigate the genetic susceptibility in T helper type 17 (Th17) cell signal transduction pathways for promoting psoriasis, we performed candidate gene and linkage disequilibrium analysis. In 208 patients and 266 normal controls, we analysed 31 single nucleotide polymorphisms in 12 genes ( CAMP, IL17A, IL17F, IL17RA, IL22, JAK1, JAK2, JAK3, STAT3, TLR7, TLR9 and TYK2 ; abbreviations: CAMP, human cathelicidin antimicrobial peptide; STAT-3, signal transducer and activator of transcription 3; TLR, Toll-like receptor; TYK2, tyrosine kinase 2). Patients with psoriasis showed a strong association for IL17F rs763780 [odds ratio (OR) = 3·27, P = 0·04], which results in a histidine-to-arginine substitution, and JAK2 rs2274471 (OR = 2·66, P = 0·02). In addition, JAK2 rs7849191 showed a protective pattern, met the significance threshold (OR = 0·77, P = 0·05) and showed a tendency for an inverse association with the frequency of early-onset psoriasis under age 40 years ( P = 0·07). In haplotype analysis, JAK1 rs310241A/rs2780889T showed a protective effect (OR = 0·73, P = 0·03) in psoriasis. In conclusion, we report two new psoriasis-susceptibility loci, in IL17F and JAK2, as well as a newly identified late-onset associated protective JAK2 locus and a protective JAK1 haplotype in the Korean population. Graphical Abstract: